Screwworm flies as agents wound myiasis - Hall, M.J.R.
(Fr, Es)
Ilus., 26 ref.
Keywords: GANADO BOVINO; INFESTACION; HERIDA; LARVAS; DIPTERA; VECTORES; COCHLIOMYIA HOMINIVORAX; MIASIS; PIEL (ANIMAL); ITALIA; REVISTA MUNDIAL DE ZOOTECNIA